A critical comparison between the semisitting and the supine positioning in vestibular schwannoma surgery: Subgroup analysis of a randomized, multicenter trial - Scheller, Christian; Rampp, Stefan; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver; Bischoff, Barbara; Matthies, Cordula; Westermaier, Thomas; Pedro, Maria Teresa; Rohde, Veit; von Eckardstein, Kajetan; et al. (Journal of Neurosurgery, 2020)
OBJECTIVE Patient positioning in vestibular schwannoma (VS) surgery is a matter of ongoing discussion. Factors to consider include preservation of cranial nerve functions, extent of tumor resection, and complications. The objective of this study was to determine the optimal patient positioning in VS surgery. METHODS A subgroup analysis of a randomized, multicenter trial that investigated the efficacy of prophylactic nimodipine in VS surgery was performed to investigate the impact of positioning (semisitting or supine) on extent of resection, functional outcomes, and complications. The data of 97 patients were collected prospectively. All procedures were performed via a retrosigmoid approach. The semisitting position was chosen in 56 patients, whereas 41 patients were treated while supine. RESULTS Complete resection was obtained at a higher percentage in the semisitting as compared to the supine position (93% vs 73%, p = 0.002). Logistic regression analysis revealed significantly better facial nerve function in the early postoperative course in the semisitting group (p = 0.004), particularly concerning severe facial nerve paresis (House-Brackmann grade IV or worse; p = 0.002). One year after surgery, facial nerve function recovered. However, there was still a tendency for better facial nerve function in the semisitting group (p = 0.091). There were no significant differences between groups regarding hearing preservation rates. Venous air embolism with the necessity to terminate surgery occurred in 2 patients in the semisitting position (3.6%). Supplementary analysis with a 2-tailed permutation randomization with 10,000 permutations of treatment choice and a propensity score matching showed either a tendency or significant results for better facial nerve outcomes in the early postoperative course and extent of resection in the semisitting group. CONCLUSIONS Although the results of the various statistical analyses are not uniform, the data indicate better results concerning both a higher rate of complete removal (according to the intraoperative impression of the surgeon) and facial nerve function after a semisitting as compared to the supine position. These advantages may justify the potential higher risk for severe complications of the semisitting position in VS surgery. The choice of positioning has to consider all individual patient parameters and risks carefully.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Acoustic neuroma; Facial nerve; Semisitting position; Supine position; Vestibular schwannoma